2000
DOI: 10.1017/s0031182099006320
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of rhoptry development in Plasmodium falciparum erythrocytic schizonts

Abstract: Prior to the separation of merozoites from the Plasmodium falciparum schizont, various stage-specific organelles are synthesized and assembled within each merozoite bud. The apical ends of the merozoites are initiated close to the ends of endomitotic spindles. At each of these sites, the nuclear membrane forms coated vesicles, and a single discoidal or cup-like Golgi cisterna appears. Reconstruction from serial sections indicates that this structure receives vesicles from the nuclear envelope and in turn gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
118
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 0 publications
16
118
0
1
Order By: Relevance
“…Importantly, both the ROP2⌬ mutant and the L529A/L530A mutant substantially colocalized with a multivesicular endosomal compartment marked by the endosomal marker VPS4 (vacuolar protein sorting-4). 4 Altogether, these data provide further evidence that rhoptry targeting occurs along the endocytic pathway and is mediated by adaptins. They also implicate adaptin machinery in mediating targeting from a post-Golgi compartment to a mature secretory organelle.…”
Section: Mutation Of Dileucine Residues In Rop2 Abolishesmentioning
confidence: 60%
See 1 more Smart Citation
“…Importantly, both the ROP2⌬ mutant and the L529A/L530A mutant substantially colocalized with a multivesicular endosomal compartment marked by the endosomal marker VPS4 (vacuolar protein sorting-4). 4 Altogether, these data provide further evidence that rhoptry targeting occurs along the endocytic pathway and is mediated by adaptins. They also implicate adaptin machinery in mediating targeting from a post-Golgi compartment to a mature secretory organelle.…”
Section: Mutation Of Dileucine Residues In Rop2 Abolishesmentioning
confidence: 60%
“…These are flask-shaped secretory organelles that are assembled and positioned at the apical pole of the invasive forms of Apicomplexa (reviewed in Refs. [2][3][4]. At the onset of host cell invasion, prepackaged proteins and membranous materials from rhoptries are secreted through an apical opening.…”
mentioning
confidence: 99%
“…Parasitespecific secretory organelles include dense granules (constitutive secretory vesicles), micronemes (regulated secretory organelles involved in host cell attachment and invasion) and rhoptries (regulated secretory organelles involved in establishment and maintenance of the intracellular parasitophorous vacuole) (Carruthers and Sibley, 1997;Joiner and Roos, 2002). Previous reports have suggested that these organelles may be synthesized de novo, within each daughter cell, during endodyogeny (Ogino and Yoneda, 1966;Sheffield and Melton, 1968;Bannister et al, 2000b). This process could be visualized by time-lapse microscopy of fluorescently labelled parasites, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…To address this situation, we have begun a detailed structural analysis of P. falciparum merozoite development, paying special attention to the role of the cytoskeleton. Peripheral microtubules are present in all invasive stages of Plasmodium [as in related apicomplexan genera (Morrissette and Sibley, 2002)] although, in P. falciparum merozoites, they are represented minimally by a band of just two or three (Bannister and Mitchell, 1995;Hopkins et al, 1999;Bannister et al, 2000;Bannister et al, 2001). Merozoite microtubules are destabilized by treating schizonts with colchicine and dinitroanilines, and this might be the root cause of the inhibitory effects of these compounds on merozoite During the assembly of Plasmodium falciparum merozoites within the schizont stage, the parasite synthesizes and positions three sets of secretory vesicles (rhoptries, micronemes and dense granules) that are active during red cell invasion.…”
mentioning
confidence: 99%